Quantitative analysis and correlation evaluation on taste quality of green tea - Chen Meili; Tang Desong; Gong Shuying; Yang Jie; Zhang Yingbin (浙江大学学报. 农业与生命科学版)
There are many of green teas with different characteristics in China, and their qualities are often evaluated by sensory evaluation without quantifying chemical compounds. Though sensory characteristics are identified quickly, the contents of compounds are unknown. Determination of chemical compounds is usually used for tea quality evaluation and the results are relatively accurate and objective. But most of the studies focus on analyzing chemical compounds of a single flavor type. Reports about comparison of main compounds in different taste types are rare. So the chemical compounds of different taste types of green tea were quantified and their relationships with the taste quality were analyzed in this study to understand the material basis of formation of different taste types in green tea.Forty-eight typical green teas in seven different taste types were selected from 287 tea samples by sensory evaluation. Thirteen chemical factors including tea polyphenols, amino acids, water extract, and caffeine were determined by standard methods. The relationships between compound contents and the taste quality were analyzed using SPSS (statistic package for social science) 16.0 software, and the tea quality predicting model based on the chemical compounds was established, which can provide certain methods for judgment of tea quality. Furthermore, the degree of correlation between every property and chemical components was carried out.The results indicated that the ester catechins, especially epigallocatechin gallate (EGCG) had a great contribution to the astringency. The green tea samples with astringency were of the high contents of water extract, tea polyphenols, ester catechins and EGCG. The green tea samples with strong taste were of high content of water extract. And the green teas with tastes of mellow, sweet and brisk were related to the low content of water extract and high content of amino acids. The factors of total water extracts, EGCG, gallic acid (GA), caffeine and gallocatechin gallate (GCG) showed stronger correlation with tea quality. The equation based on stepwise regression analysis had good predictive ability for the taste quality and total quality, and the right ratios for taste score and total quality score were 79% and 83% respectively. Furthermore, the water extract, EGCG, caffeine, GCG, epicatechin gallate (ECG) and tea polyphenols were well related to the divided taste properties.In conclusion, different kinds of taste characteristics are based on different contents of chemical components in green tea.